(untitled) (Innovative professional education, 2024)
In the conditions of the pandemic and martial law, blended learning in Ukraine has gained relevance and development. Accordingly, monitoring the quality of education of future qualified workers in the conditions of blended learning becomes relevant. In this work, the author provides an understanding of monitoring in professional (vocational and technical) education and its components in domestic science. He conducts a theoretical analysis of the criteria and indicators for assessing the quality of education in modern theory and practice, in particular, the criteria and indicators for assessing the quality of distance education in the conditions of blended learning.